Simple Extraction of Dragon Fruit (Hylocereus polyrhizus) Peel as Natural Dye Colorant - Sudarmi, Sri; Subagyo, Purwo; Susanti, Anna; Wahyuningsih, Anggun Sri (Eksergi, 2015)
Natural dyes can be obtained from the pigments that contained from leaves, fruit, and rind of the plants. Dragon fruit peel is one of the potential natural pigment source. Almost 30-35% of the peel fruit is often simply thrown away as trash. Dragon fruit peel provides natural red color produced by pigment called anthocyanin which can be used as a subtituent from synthetic dyes to natural dyes. This research was objected to find the optimum conditions for anthocyanin extraction of dragon fruit peel. Simple extraction was carried out by using 80% ethanol solvent with variable ratio of the amount of material and solvent (1: 9 to 1:13), temperature (50◦ to 80◦ C) and time (1 to 5 hours). Optimum result was obtained from a ratio F: S 1:11, temperature 50◦C, for 3 hours.